Syndrome D’aniridie Associé À La Dermatite Atopique: À Propos D’un Cas - Kaka H.Y, Abba; L., Salissou; A., Amza; M., Daou (European Scientific Journal, ESJ, 2016)
Aniridia syndrome is a genetic anomaly affecting all ocular structures; it is transmitted by an autosomal dominant mode. In its isolated form aniridia is characterized by a hypoplasia of the iris frequently associated with other ocular anomalies. It the syndromic form it is associated to other systemic abnormalities. Authors are here reporting a case of aniridia associating: a corneal pannus, total aniridia, lens ectopia, and cataract found in a 14 years old girl. She also presented an atopic background with a positive family history of atopia. She is issued from a first degree consanguineous marriage. The management was multidisciplinary. In ophthalmology she underwent an intra-capsular extraction of the lens in both eyes with no intra-ocular lens implantation. Dermatological management was treatment of cuteanous lesions with emollients, corticoids and antihistamines drugs and ointments.